2009
DOI: 10.1002/14651858.cd007086.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystectomy for suspected gallbladder dyskinesia

Abstract: The evidence for the benefits and harms of cholecystectomy in gallbladder dyskinesia from randomised clinical trials is based on a single small trial at risk of bias. Further randomised clinical trials with improved bias control are necessary to confirm or reject the promising results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…The findings of this audit support the view of the Cochrane Collaboration that randomized clinical trials are needed to assess the role of cholecystectomy in the management of ABP [3]. The audit provides evidence that relaxation of the SO using BTX may have a place in the management of ABP and warrants further investigation.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The findings of this audit support the view of the Cochrane Collaboration that randomized clinical trials are needed to assess the role of cholecystectomy in the management of ABP [3]. The audit provides evidence that relaxation of the SO using BTX may have a place in the management of ABP and warrants further investigation.…”
Section: Discussionsupporting
confidence: 64%
“…Laparoscopic cholecystectomy (LC) is the most common intervention recommended for the treatment of ABP, but controversy remains regarding its efficacy [2]. A Cochrane Collaboration review published in 2009 [3] found that the evidence for the benefits and harms of cholecystectomy in ABP from randomized clinical trials is based on a single trial involving 21 patients that is at risk of bias and was conducted during the era of open cholecystectomy [4].…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis examining the effectiveness of CCY, Ponsky et al [7] concluded that 98% of patients reported complete or partial symptom relief after CCY. A Cochrane review article was published in 2009 [62] to study the efficacy of CCY for BD, but the authors were able to include only one study, the prospective study conducted by Yap et al [36], and concluded that the level of evidence is not sufficient to recommend CCY for patients with GBD and that further randomized clinical trials are needed. Table 2 compares studies evaluating the effect of CCY on the symptoms of GBD.…”
Section: Treatmentmentioning
confidence: 99%
“…Patients with symptoms of biliary obstruction without evidence of gallstones but with abnormal gallbladder emptying may benefit from laparoscopic cholecystectomy [87][88][89][90][91][92]. Symptoms may include episodic, severe, steady pain, frequently with fatty food intolerance, located in the right upper quadrant or epigastrium, with or without radiation to the back or shoulder lasting at least 30 min but less than several hours, and may potentially be associated with nausea and vomiting [89,90].…”
Section: Biliary Dyskinesiamentioning
confidence: 99%